Evaluation and management of dental affections in dogs - Archana A (Department of Veterinary Surgery and Radiology, College of Veterinary and Animal Sciences, 2009)
The prevalence of various dental diseases among dogs and its relation with age, breed, sex and food habits were studied in dogs presented to the Veterinary College Hospitals during a period from April 2008 to December 2008 and found that 102 were affected with dental and periodontal diseases. Among of the 102 dogs affected, prevalence of dental affection noticed were dental tartar, epulis, oral ulcer and dental attrition in descending order. Incidence of dental affections was more in dogs in age group of five to eight years (45.09%), followed by one to four years (37.25%) and nine to twelve years (17.65%). The prevalence of dental disorders in different breeds were: German Shepherd Dog (26.47%), Spitz (20.59%), Dachshund(14.71%), Labrador Retriever (11.76%), Non-descript (8.82%), Doberman Pinscher (4.90%), Cocker Spaniel (3.92%), Rottweiler and Chinese Pug (1.96% each) and Boxer, Great Dane, Basset hound, Lhasa Apso and Miniature Pinscher (0.98% each). Females (51.96%) were found affected more than males (48.04%). Dental affections was found high in those dogs fed with soft diets like homemade food (71.1%), titbits (81.8%) and in those not fed bones (78.72%). Out of 102 dogs with dental affections, 24 cases were randomly selected for detailed study. The dogs were belonged to various breeds like Spitz, Cocker Spaniel, Labrador Retriever, German Shepherd Dog, Non - descript, Doberman Pinscher, Dachshund, Boxer and Miniature pinscher of either sex (16 females and 8 males), with an average age of 5.79 ± 0.66 years. The clinical condition included dental tartar (79.17%), epulis (12.5 %) and Oral ulcer (8.33%). The most predominant bacteria isolated by the culture of gingival sulcus swabs were Gram-negative cocco-bacillary organisms (71.43%) followed by Gram positive cocci (28.57%). The former were highly sensitive to ciprofloxacin, enrofloxacin, cefotaxime and the latter to amoxycillin, ampicillin and enrofloxacin. Successful medical treatment was given for two cases with gingivitis and ulceration of buccal mucosa using an antibiotic, orally and intra oral application of metronidazole gel. Two cases of gingival tumour were treated with vincristine, but no response was noticed. Surgical techniques included ultrasonic dental scaling, exodontia and surgical excision of tumour was performed under general anaesthesia. Dogs with severe gingivitis, halitosis and dental calculus were effectively treated with ultrasonic dental scaling followed by oral and local administration of antibiotics. Exodontia was performed in three cases in which the tooth was shaky and with furcation exposure. One case of gingival tumour case treated with surgical excision with cryodestruction, showed recurrence of tumor after three weeks.